2016
DOI: 10.1177/0284185116653280
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of degenerative changes of the posterior cruciate ligament

Abstract: Background Mucoid degeneration and ganglia reflect a continuum of degenerative changes within the posterior cruciate ligament (PCL). Purpose To assess the prevalence of and radiologists' familiarity with PCL mucoid degeneration and ganglia. Material and Methods Knee magnetic resonance imaging (MRI) from July 2013 to June 2015, excluding patients who had a preceding trauma or MRI findings indicative of a prior injury, were retrospectively reviewed, with the specific request to assess degenerative changes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The clinical diagnosis of a PCL injury can be challenging with conventional magnetic resonance (MR) imaging for diagnosing both acute and chronic PCL injuries (DePhillipo et al, 2018; Orakzai et al, 2010; Servant et al, 2004; Tewes et al, 1997). When a PCL tear is suspected, radiologists will commonly examine the patient’s MR images for secondary signs such as PCL thickening, increased signal or elongation (Cho et al, 2001; Draghi et al, 2017; Geeslin et al, 2017; Rodriguez et al, 2008). However, several authors have reported that the appearance of the PCL on conventional MR imaging is not reliable in predicting its functional integrity or degenerative changes (Akisue, Kurosaka, Yoshiya, Kuroda, and Mizuno, 2011; McMonagle et al, 2013; Orakzai et al, 2010; Rodriguez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis of a PCL injury can be challenging with conventional magnetic resonance (MR) imaging for diagnosing both acute and chronic PCL injuries (DePhillipo et al, 2018; Orakzai et al, 2010; Servant et al, 2004; Tewes et al, 1997). When a PCL tear is suspected, radiologists will commonly examine the patient’s MR images for secondary signs such as PCL thickening, increased signal or elongation (Cho et al, 2001; Draghi et al, 2017; Geeslin et al, 2017; Rodriguez et al, 2008). However, several authors have reported that the appearance of the PCL on conventional MR imaging is not reliable in predicting its functional integrity or degenerative changes (Akisue, Kurosaka, Yoshiya, Kuroda, and Mizuno, 2011; McMonagle et al, 2013; Orakzai et al, 2010; Rodriguez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that MRI is not useful enough to analyze the quality within the ligaments which have a short echo time [2], the measurement of CT HU value could be a valid method to provide us more details about the ligament property. Although further studies are required, the evaluation using the CT HU value could be applied not only for PCL but also for other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI is only useful to detect rupture, mucoid degeneration and ganglion in PCLs and it is not enough to analyze the quality within the ligaments which have a short echo time [2]. On the other hand, computed tomography (CT) scan is also one of the conventional modalities to assess knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been commonly used to evaluate PCL degeneration. However, MRI is only useful for detecting rupture, mucoid degeneration, and ganglion in PCLs; it is not sensitive enough to analyze the quality within the ligaments that have a short echo time [2]. Conversely, computed tomography (CT) is a conventional modality used to assess knee OA.…”
Section: Introductionmentioning
confidence: 99%